2018
DOI: 10.3390/s18103248
|View full text |Cite
|
Sign up to set email alerts
|

Odorant-Binding Proteins as Sensing Elements for Odour Monitoring

Abstract: Odour perception has been the object of fast growing research interest in the last three decades. Parallel to the study of the corresponding biological systems, attempts are being made to model the olfactory system with electronic devices. Such projects range from the fabrication of individual sensors, tuned to specific chemicals of interest, to the design of multipurpose smell detectors using arrays of sensors assembled in a sort of artificial nose. Recently, proteins have attracted increasing interest as sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 89 publications
0
64
0
Order By: Relevance
“…heat stress) can cause proteins to misfold and denature, resulting in a loss of biological function [74,75]. However, such heat denaturation of proteins involved in olfaction remains unlikely since they are particularly stable to thermal denaturation [76]. Exposure of pollinators to high temperatures may nevertheless induce serious damages such as denaturation of non-antennal proteins, disturbance of the nervous and endocrine systems, damage to DNA but also the alteration of the liquid-crystalline fluidity of the membrane, which could disrupt the whole organism and lead to death ( [77], reviewed in [78]).…”
Section: Disruption To Host Attraction and Foraging Behavioursmentioning
confidence: 99%
“…heat stress) can cause proteins to misfold and denature, resulting in a loss of biological function [74,75]. However, such heat denaturation of proteins involved in olfaction remains unlikely since they are particularly stable to thermal denaturation [76]. Exposure of pollinators to high temperatures may nevertheless induce serious damages such as denaturation of non-antennal proteins, disturbance of the nervous and endocrine systems, damage to DNA but also the alteration of the liquid-crystalline fluidity of the membrane, which could disrupt the whole organism and lead to death ( [77], reviewed in [78]).…”
Section: Disruption To Host Attraction and Foraging Behavioursmentioning
confidence: 99%
“…They are smaller than ORs (approximately 20 kDa) and much more stable to temperature change, pH variations, and organic solvents. Moreover, they are soluble, which greatly facilitates their expression by bacteria and their use in sensors [34][35][36]. Mammalian OBPs belong to the lipocalin family.…”
Section: Bio-sourced Materialsmentioning
confidence: 99%
“…Although OBPs are more stable than other proteins, they can lose their active conformation in harsh conditions. Thus, an aqueous medium is required to ensure their function [36]. Humidity remains an important issue when it comes to peptides, although less structured and so, more robust than proteins when dried.…”
Section: Hydrated Sensing Environmentmentioning
confidence: 99%
“…An extensive literature survey revealed that these typically include Odorant-binding proteins (OBPs), D7proteins, Chemosensory proteins (CSPs) and Niemann-Pick C2 type proteins (NPCs). Protein families of OBPs, CSPs and NPC2 are secretory in nature with an N-terminal signal peptide (Pelosi et al, 2018).…”
Section: Soluble Proteins In Chemical Communication Remain Dissolved mentioning
confidence: 99%
“…NPC2 proteins share some structural and functional characteristics with odorant-binding proteins (OBPs) and chemosensory proteins (CSPs), soluble polypeptides involved in detection and delivery of semiochemicals in vertebrates and in insects (Vogt and Riddiford, 1981;Angeli et al, 1999;Pelosi et al, 2014Pelosi et al, , 2018). As OBPs and CSPs, also NPC2 proteins present a signal peptide revealing their secretory nature.…”
Section: Soluble Proteins In Chemical Communication Remain Dissolved mentioning
confidence: 99%